Effect of different acidulants on shelf life of chhana podo at ambient temperature - S. S. Bankar; M. Raziuddin; P.N. Zanjad; Adil Shaikh (Indian Journal of Veterinary and Animal Sciences Research, 2023)
Present study was undertaken to evaluate the shelf life of chhana podo prepared from 1% citric acid and 2% lactic acid and stored at ambient temperature (30+ 20 C). Microbial, physico-chemical and sensory qualities of product were studied during storage. The chhana podo were analyzed Standard Plate Count (SPC), yeast and mould count on alternate days. The SPC, yeast and mould count increased significantly (P<0.05) with the progress of storage at ambient temperature in 1% citric acid and 2% lactic acid products. No significant change in SPC, yeast and mould count was observed up to 2nd day storage but later there was remarkable increase in SPC (2.79 & 2.55) as well as yeast and mould count (12.40 & 12.30) at the end of day four. The significant reduction in pH, moisture and fat content in 1% citric acid and 2% lactic acid products during the progress of storage of 8 days, while protein content showed an increasing trend. All the sensory quality attributes of products made by 1% citric acid and 2% lactic acid were comparable up to 2 days of storage from then on declined significantly with progress of storage. Colour, body & texture, flavour and overall acceptability score of channa podo declined significantly up to the 4th days of storage. Thus, the findings of the study indicated that the channa podo could be safely stored upto 4th days at ambient temperature.